Internet Banking Anti-Cybercrime - Nanang Setiawan (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
This paper aims to explain the reality of cybercrime cases in Internet banking and provide alternative prevention to minimize the occurrence of cyber crimes in Internet banking in Indonesia. This article uses a descriptive qualitative method with a literature study approach. Cybercrime is a white-collar crime, the perpetrators are educated people who have a great curiosity about computer technology and who see the opportunity for negligence from computer users (especially access to banking) and also a weak network security system and rationalization get a large benefit with low risk. Preventive actions to avoid cyber-crime are to constantly increase knowledge of the modus of cyber-crime and how to deal with it, to be extra careful in every transaction and access to banking either through cellular or computers, be extra careful with every data, passwords, PINs and other banking codes and make changes regularly, and not easily tempted from irresponsible people